MENINGKATKAN MOTIVASI MENGHAFAL AL-QUR’AN SANTRI MADRASAH AL-HIDAYAH DAN AKSI PEDULI LANSIA PASIR SALAM - Ayudia, Dinne Rahma; Sastriana, Reva; Amrullah, Fahmi; Wandansari, Sarah Adilah; Supala, Supala (Universitas Islam Negeri Raden Intan Lampung, 2021)
The target of this community service is the Pasir Salam area located in Ancol Village, Regol Subdistrict, Bandung City. When the Covid-19 pandemic hit the world, it greatly impacted the elderly people who were poorly met with basic needs and also their health. In addition, the low motivation to memorize the Qur’an among santri to accommodate the need for religious support. This community service aims to help elderly people who are less fulfilled basic needs and health. Then re-cultivate the motivation of learning in memorizing the Qur’an among santri to accommodate the needs of religious support in the Pasir Salam area. Methods used through the process of observation, interview, and practice directly from the results of the implementation of several main programs and support programs. The results of the main program activities and supporting programs show the success rate with the action of caring for the elderly through donations from the local community to help the basic needs and health of the RW 09 Elderly (Pasir Salam), the implementation of fun learning methods that are in harmony with the conditions of the santri in pasir salam area, and the existence of other activities that trigger community sensitivity to social and religious activities in Pasir Salam. It is determined to have gone well, although some of them have been constrained, but can still be implemented. Therefore, in order to maintain the continuity of the entire program after devotion required the participation of all elements.